2014
DOI: 10.1111/clr.12385
|View full text |Cite
|
Sign up to set email alerts
|

Marginal bone and soft tissue behavior following platform switching abutment connection/disconnection– a dog model study

Abstract: Marginal bone and soft tissue behavior following platform switching abutment connection/disconnection -a dog model study PhD THESIS Célia Coutinho AlvesAutorización do Director / Tutor da Tese (RD 778/1998) RESUMENLa literatura científica parece indicar que la conexión/desconexión del pilar protésico puede provocar alteraciones en la inserción epitelial, causando sangrado y ulceración en el mismo. Esta ruptura mecánica se puede considerar como una herida abierta con la exposición del tejido conjuntiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 158 publications
1
21
0
6
Order By: Relevance
“…The other areas were used for another experimental study that has been recently published (Alves et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other areas were used for another experimental study that has been recently published (Alves et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental area was located at the level of the second premolar region in each side of the mandible. The other areas were used for another experimental study that has been recently published (Alves et al 2015).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…They observed that abutment handling resulted in marginal bone resorption due to tissue reactions initiated to establish proper biological width, which moved the mucosal barrier apically relative to the soft tissue. Other factors, such as microgaps between the implant and abutment (10), micromovement at the implant-abutment interface (11), microleakage between the implant and abutment (8), and abutment disconnection and/or reconnection (1-3) also affect bone remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…; Alves et al. ) and in humans mainly in combination with immediate single implant placement (Canullo et al. ; Degidi et al.…”
mentioning
confidence: 99%
“…This experimental evidence prompted the development of the "one abutment at one-time" protocol consisting on the placement of the definitive restorative abutment at the time of implant surgery, thus avoiding its removal during healing. This protocol has been tested in animal models (Becker et al 2012;Rodr ıguez et al 2013;Alves et al 2015) and in humans mainly in combination with immediate single implant placement (Canullo et al 2010;Degidi et al 2014, Grandi et al 2014). The scientific evidence on its efficacy when applied to implants placed in healed sites is, however, unclear (Degidi et al 2011;Grandi et al 2012).…”
mentioning
confidence: 99%